Lectures on Antitrust Economics, Chapter 1: Introduction - Michael D. Whinston (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
Antitrust laws play a prominent role in the business environment of many nations. Indeed, if one is a regular reader of the New York Times or Wall Street Journal, the chances are good of seeing in any given week at least one, and often several, articles devoted to some aspect of antitrust policy, whether about a recently announced merger of two large oil companies, a case alleging that an important software company has violated the antitrust laws by suppressing competition, or the revelation that a group of international firms producing an important feed additive have conspired to fix prices. The same can increasingly be said of newspapers in many capitals around the world. These lectures are intended to serve as an introduction to the economics behind antitrust policies. The lectures do not strive to be comprehensive in their coverage. Rather, I focus selectively on some of the most recent developments in antitrust economics, and on some areas in which I believe there are important open issues requiring further research. As a result, I do not discuss several significant areas of antitrust economics, including - for example - predatory pricing and restrictions on intrabrand competition such as resale price maintenance. In the frst part of the lectures I discuss two topics - price-fixing and horizontal mergers - that involve horizontal collaboration among firms; that is, collaboration among firms at the same stage of the production/distribution chain. In the second part I turn my attention to three potentially exclusionary practices - exclusive dealing, tying, and vertical integration - that involve contracts between entities located at different levels of the production/distribution chain; so-called vertical practices.
Keywords: 330; Konzentrationspolitik; Kartellrecht; Preisabsprache; Fusionskontrolle; USA